2009
DOI: 10.1177/1559827609342198
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aerobic and Resistance Exercise on the Health of HIV-Infected Persons

Abstract: Individuals infected with HIV experience numerous comorbidities caused by the disease progression and medications, lack of (or inability to perform) physical activity, malnutrition, or a combination of these causes. Common symptoms include loss of muscle mass, fatigue, lypodystrophy, lypoatrophy, and decreases in strength, functional capacity, and overall quality of life. Studies have shown that exercise is a potential treatment of many of these symptoms. Research suggests that exercise may produce beneficial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 29 publications
3
48
0
Order By: Relevance
“…In a 2009 review, Hand et al [23] summarized the results of numerous studies of HIV-infected patients which examined both aerobic exercise and resistance training. In the studies employing aerobic exercise, the outcomes showed significant reductions in anxiety and depression as well as significant increases in maximal oxygen uptake (VO 2max ) and decreases in body mass index (BMI), total cholesterol and triglycerides, body fat, and abdominal girth.…”
Section: Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…In a 2009 review, Hand et al [23] summarized the results of numerous studies of HIV-infected patients which examined both aerobic exercise and resistance training. In the studies employing aerobic exercise, the outcomes showed significant reductions in anxiety and depression as well as significant increases in maximal oxygen uptake (VO 2max ) and decreases in body mass index (BMI), total cholesterol and triglycerides, body fat, and abdominal girth.…”
Section: Exercisementioning
confidence: 99%
“…The patients executed 2-3 sets with 8-10 repetitions. The weight of the repetition was determined to be 60-80 % of one repetition max [23,25].…”
Section: Exercisementioning
confidence: 99%
“…30 Although the overall effect of physical activity on HIVinfected individuals has been confi rmed, most studies have not demonstrated an eff ect on viral load or immunological indices. 28 Nonetheless, the safety of physical participation and its positive contribution to the psychological wellness of the HIV population has been established. 31 Although in the study by Dolan and co-workers 32 there were no signifi cant diff erences in blood glucose levels, CD4+ cell count or viral load the impact of a supervised home-based exercise program on the physical strength, cardio-respiratory health and endurance levels of a small group of HIV-infected women has been documented in that study.…”
Section: Discussionmentioning
confidence: 99%
“…28 Moderate physical activity is considered to be safe in stable HIV-infected persons, and may off er substantial physiological and psychological benefi ts. 29 Within the context of the present study, physical activity revolving around social and typical household activities, may have played a signifi cant role in maintaining the general well-being 15 of the HIV-infected women.…”
Section: Discussionmentioning
confidence: 99%
“…7,11,[18][19][20] The use of a home-based physical activity intervention in other clinical populations has successfully increased the amount of daily physical activity accumulated when compared to a control group. 12,21,22 These programs incorporated moderate-intensity physical activity, which has been shown to be safe for clinical populations with functional limitations.…”
Section: Introductionmentioning
confidence: 99%